2019
DOI: 10.1080/24750573.2019.1636483
|View full text |Cite
|
Sign up to set email alerts
|

The effects of childhood emotional abuse on aggressive obsessions among patients with obsessive compulsive disorder may be mediated by symptoms of depression and anxiety

Abstract: OBJECTIVE: The purpose of this study was to evaluate the relationship between childhood traumas (CTs) and severity and symptom dimensions of Obsessive Compulsive Disorder (OCD). METHOD: One hundred and sixty (160) patients diagnosed with OCD were included. The Yale-Brown Obsessive-Compulsive Scale (YBOCS), the Childhood Trauma Questionnaire (CTQ), the Beck Depression Inventory (BDI), and the Beck Anxiety Inventory (BAI) were applied to the participants. RESULTS: According to a cutoff score of > 35 for CTQ tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…All of the ten included studies ( 19 21 , 23 , 34 39 ) employed a cross-sectional design except for Wang et al ( 39 ) and Bey et al ( 20 ), which employed a case-control design. All studies used the Yale Brown Obsessive Compulsive Scale (YBOCS) to evaluate the severity of the OCS in OCD patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the ten included studies ( 19 21 , 23 , 34 39 ) employed a cross-sectional design except for Wang et al ( 39 ) and Bey et al ( 20 ), which employed a case-control design. All studies used the Yale Brown Obsessive Compulsive Scale (YBOCS) to evaluate the severity of the OCS in OCD patients.…”
Section: Resultsmentioning
confidence: 99%
“…As is well-known, studies of comorbidity in OCD have reported that OCD sufferers are often accompanied by a high level of depressive symptoms ( 2 4 , 18 ). A clinical study that enrolled 160 patients diagnosed with OCD found a higher depressive level in the childhood trauma (CT)-exposed group than non-CT exposed group ( 19 ). Moreover, empirical studies have pointed out the unique relationship between the CM and the severity of depressive symptoms in OCD ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent research, however, suggests that traumatic experiences could hinder ability to understand the views and feelings of others (Jonathan et al., 2019). Childhood trauma is a known risk factor for numerous psychopathologies in adulthood, including aggressive behaviours (Gorodetsky et al., 2014; Karatzias et al., 2018; Kart & Türkçapar, 2019). Further, trauma, both experienced and witnessed, is often repeated into adulthood (Maniglio, 2009; Nancy & Jing, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The point to note is that childhood emotional maltreatment (CEM; i.e., emotional abuse and neglect), which is a vulnerable factor for psychopathology (Taillieu et al, 2016) when maladaptive coping is widely used (Bell & Higgins, 2015;Khosravani, Messman-Moore, et al, 2019), has also been found to have a more important role than other aspects of childhood maltreatment in OCD symptoms (Mathews et al, 2008;Renkema et al, 2020;Wang et al, 2020), such as unacceptable thoughts and responsibility for harm in particular (Berman et al, 2013;Kart & Türkçapar, 2019;Rukiye & Erbay, 2018).…”
mentioning
confidence: 99%